2007
DOI: 10.1097/01.tp.0000256178.57359.4f
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functional Islet-Like Clusters After Monolayer Culture and Intracapsular Aggregation of Adult Human Pancreatic Islet Tissue

Abstract: Collectively, these data indicate that adult human pancreatic islet cells can be expanded by three serial passages while maintaining their endocrine properties and can yield functional islet-like cell clusters through intracapsular aggregation that reverse hyperglycemia in diabetic mice. This culture and aggregation process could serve as a platform for proliferation and differentiation studies of endocrine lineage cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Consistent with this view, it is well established that the dispersal of isolated rodent islets into single cells results in poor insulin secretory responsiveness compared with intact islets (Lernmark 1974, Halban et al 1987, Tsang et al 2007. By contrast, dispersed islet cells have also been reaggregated in culture into islet-like structures with restoration of cellular architecture and the original insulin secretory properties of intact islets (Hopcroft et al 1985, Halban et al 1987, Squires et al 2000.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with this view, it is well established that the dispersal of isolated rodent islets into single cells results in poor insulin secretory responsiveness compared with intact islets (Lernmark 1974, Halban et al 1987, Tsang et al 2007. By contrast, dispersed islet cells have also been reaggregated in culture into islet-like structures with restoration of cellular architecture and the original insulin secretory properties of intact islets (Hopcroft et al 1985, Halban et al 1987, Squires et al 2000.…”
Section: Introductionsupporting
confidence: 56%
“…The global nature of the benefits for insulin secretion of configuration of 1.1B4 cells as pseudoislets points to a fundamental role of three-dimensional cell-to-cell communication in human b-cell function, which is supported by observations with disrupted human islets (Tsang et al 2007). However, these data also suggest that homotypic pseudoislet interactions may be largely sufficient for integrated insulin secretion from human-derived b cells, despite the obvious lack of islet glucagon-or somatostatinproducing cells.…”
Section: Discussionmentioning
confidence: 62%
“…As far as we know, proliferation of postnatal islet cells is relatively low compared with tissues such as intestines or bone marrow, except in states favouring robust beta cell growth, such as pregnancy, insulin resistance, and obesity (Bouwens and Rooman, 2005;Heit et al, 2006). Experimental data indicate that adult human pancreatic islet cells can be expanded by three serial passages while maintaining their endocrine properties and can yield functional islet-like cell clusters through aggregation in alginate-poly-L-lysine microcapsules that reverse hyperglycaemia in diabetic mice (Tsang et al, 2007). It has been also demonstrated that foetal pancreatic cells differentiate and function normally when placed within barium alginate microcapsules and transplanted (Foster et al, 2007).…”
Section: Pancreatic Progenitor Cellsmentioning
confidence: 96%
“…Tsang et al aggregated adult human pancreatic islet cells in the intracapsular spaces of alginate-polyl-lysine microcapsules. 53 These capsules had potent effects on reducing hyperglycemia and produced human C-peptide after transplantation into mice.…”
Section: Non-adherent Dish Under Static Conditionmentioning
confidence: 99%
“…As mentioned previously, the capsulation of pseudoislets is another technique that facilitates immunoprotection and helps control the size of islets. 53 Sakai et al reported advanced methods for forming cell aggregates with outer cell layers as a model of islets. 60 Onoe et al established islet tissues by reconstituting them in hydrogel fibers.…”
Section: Production Of Bioartificial Islets Using Reconstituted Isletsmentioning
confidence: 99%